Quantum theory and symmetries with Lie theory and its applications in physics. QTS-X/LT-XII, Varna, Bulgaria, June 2017 /: QTS-X/LT-XII, Varna, Bulgaria, June 2017. Volume 2 : (2018) - Unknown
No abstract available